1985
DOI: 10.1002/esp.3290100509
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary scanning electron microscope study of honeycomb weathering of sandstone in a coastal environment

Abstract: Honeycomb weathering has been observed in a Carboniferous sandstone at a coastal location near Ballycastle on the north coast of Northern Ireland. Specimens of this sandstone have been analysed by X-ray diffraction, scanning electron microscopy, and energy dispersive spectrometry. Results reveal that calcium sulphate (gypsum) is the only salt present and is found only at and immediately below the rock surface. SEM observations suggest that crystallization of salts in pores could easily dislodge quartz grains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 19 publications
0
20
0
3
Order By: Relevance
“…Only Bartrum (1936), McGreevy (1985, Matsukura et al (1989), andRodriguez-Navarro et al (1999) appear to have addressed the origin of the honeycomb pattern itself. Bartrum suggested that the sizes and patterns were the predictable result of random, small depressions on fracture surfaces or bedding planes that grew into mature pits by salt weathering.…”
Section: −0·44mentioning
confidence: 95%
See 1 more Smart Citation
“…Only Bartrum (1936), McGreevy (1985, Matsukura et al (1989), andRodriguez-Navarro et al (1999) appear to have addressed the origin of the honeycomb pattern itself. Bartrum suggested that the sizes and patterns were the predictable result of random, small depressions on fracture surfaces or bedding planes that grew into mature pits by salt weathering.…”
Section: −0·44mentioning
confidence: 95%
“…Matsukura et al (1989) suggested that pholad clam borings served as the nucleation site of some cells. McGreevy (1985) said that the reason for the pattern was unknown. Neither Bartrum's (1936), Matsukura et al's (1989), or Rodriguez-Navarro et al's (1999 explanations apply to these Tuscan honeycombs.…”
Section: −0·44mentioning
confidence: 96%
“…Honeycomb weathering has long been reported to develop rapidly (Gill, 1981;Mustoe, 1982;Mottershead, 1994;Pye and Mottershead, 1995;Norwick et al, 2001), and it comes as a surprise to recognize that at Pacifi c Northwest sites cavity zones actually represent a retardation of erosion rate relative to adjacent planar surfaces. The apparent scarcity of NaCl residues in honeycombed outcrops (McGreevy, 1985;Young, 1987;Mottershead and Pye, 1994) can perhaps be explained by the seasonal nature of coastal salt weathering: at the present study sites, NaCl crystals were commonly observed in coastal sandstone samples collected during periods of summer dry weather, but not in wet seasons. Honeycomb cavities at a particular location commonly display great morphological diversity, with zones of newly-developed cavities occurring in proximity to areas where other cavity zones are being destroyed.…”
Section: Introductionmentioning
confidence: 73%
“…For supratidal outcrops, salt crystals are typically present within honeycomb cavities during rainfree periods during spring and summer, especially during periods when high tides are accompanied by onshore wind, increasing the amount of seawater deposited as wave splash. This seasonality perhaps explains why some researchers (McGreevy, 1985;Young, 1987;Mottershead and Pye, 1994) failed to detect the presence of salt crystals at coastal sites where honeycomb weathering occurs. Samples collected for …”
Section: Two Weathering Zones: Intertidal and Supratidalmentioning
confidence: 91%
See 1 more Smart Citation